Storm drains as larval development and adult resting sites for Aedes aegypti and Aedes albopictus in Salvador, Brazil. Issue 1 (December 2016) - Paploski, Igor; Rodrigues, Moreno; Mugabe, Vánio; Kikuti, Mariana; Tavares, Aline; Reis, Mitermayer; Kitron, Uriel; Ribeiro, Guilherme
Abstract Background Dengue (DENV), Chikungunya (CHIKV), Zika (ZIKV), as well as yellow fever (YFV) viruses are transmitted to humans byAedes spp. females. In Salvador, the largest urban center in north-eastern Brazil, the four DENV types have been circulating, and more recently, CHIKV and ZIKV have also become common. We studied the role of storm drains asAedes larval development and adult resting sites in four neighbourhoods of Salvador, representing different socioeconomic, infrastructure and topographic conditions. Results A sample of 122 storm drains in the four study sites were surveyed twice during a 4-month period in 2015; in 49.0 % of the visits, the storm drains contained water. Adults and immatures ofAedes aegypti were captured in two of the four sites, and adults and immatures ofAedes albopictus were captured in one of these two sites. A total of 468 specimens were collected: 148Ae. aegypti (38 adults and 110 immatures), 79Ae. albopictus (48 adults and 31 immatures), and 241 non-Aede s (mainlyCulex spp.) mosquitoes (42 adults and 199 immatures). The presence of adults or immatures ofAe. aegypti in storm drains was independently associated with the presence of non-Aede s mosquitoes and with rainfall of ≤ 50 mm during the preceding week. Conclusions We found that in Salvador, one of the epicentres of the 2015 ZIKV outbreak, storm drains often accumulate water and serve as larval development sites and adult resting areas for bothAe. aegypti andAe. albopictus . Vector control campaigns usually overlook storm drains, as most of the effort to preventAe. agypti reproduction is directed towards containers in the domicile environment. While further studies are needed to determine the added contribution of storm drains for the maintenance ofAedes spp. populations, we advocate that vector control programs incorporate actions directed at storm drains, including regular inspections and use of larvicides, and that human and capital resources are mobilized to modify storm drains, so that they do not serves as larval development sites forAedes (and other) mosquitoes.